2011
DOI: 10.1111/j.1753-0407.2011.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxypropyl methylcellulose on obesity and glucose metabolism in a diet-induced obesity mouse model

Abstract: Background:  To investigate the effect of hydroxypropyl methylcellulose (HPMC) on weight loss and metabolic disorders associated with obesity using a high‐fat diet‐induced obese mouse model under a high‐fat diet regimen. Methods:  Obese male C57BL/6J (B6) mice were fed either a high‐fat (60% kcal), low‐fat (10% kcal), or high‐fat diet plus HPMC (4% and 8%) for 5 weeks. Body, mesenteric adipose, and liver weights were determined at the end of the study. In addition, plasma cholesterol, insulin, glucose, adipone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
(76 reference statements)
2
20
0
Order By: Relevance
“…The risk factors associated with obesity are linked, in part, to the fat-induced hypertrophy and hyperplasia of adipocytes3536. The present data showed supplementation of a high-fat diet with bamboo shoot fiber suppressed body weight gain through suppressing hyperplasia of adipocytes.…”
Section: Discussionmentioning
confidence: 48%
“…The risk factors associated with obesity are linked, in part, to the fat-induced hypertrophy and hyperplasia of adipocytes3536. The present data showed supplementation of a high-fat diet with bamboo shoot fiber suppressed body weight gain through suppressing hyperplasia of adipocytes.…”
Section: Discussionmentioning
confidence: 48%
“…Nonetheless, both HEMC and HPMC were able to suppress the increase in blood glucose level in mice. Previous studies have shown that diet supplementation with HPMC reduced the blood glucose concentrations in obese mice [6] hamsters [14], and human subjects [7]. This glucose-lowering effect of HPMC has been attributed to its high viscosity, a common property of soluble fibers [1,2].…”
Section: Resultsmentioning
confidence: 99%
“…Hung et al . [6] also reported a decrease in the insulin level in mice fed with a high fat diet supplemented with HPMC. Moreover, consumption of high viscosity HPMC was shown to significantly blunt the postprandial glucose and insulin responses in obese men and women [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the methylcellulose fibers, the hydroxypropyl methylcellulose (HPMC) was the most studied in relation to physiological functions. It was reported to reduce body weight and normalized metabolic abnormalities in obese mice (Hung, Anderson, Albers, Langhorst, & Young, 2011) and lower serum cholesterol level in human subjects (Maki, Carson, Miller, et al, 2009;Reppas, Swidan, Tobey, Turowski, & Dressman, 2009). Recently, HEMC was found to have a hypolipidemic action similar to HPMC (Ban, Rico, Um, & Kang, 2011).…”
Section: Introductionmentioning
confidence: 97%